MAIN DETERMINANTS OF CHANGES IN PAY POLICY: REALITIES OF MARTIALLAW - KUCHABSKYI, Nazariy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the main determinants of wages and their changes that affect the level of wages in Ukraine in conditions of war and the introduction of martial law, which led to significant changes in wages and the territorial distribution of the population. The main factors that shape workers' earnings are identified, including: the level of education, professional qualifications, macroeconomic conditions, globalization, technological innovations and state regulation. The specifics of the situation on the Ukrainian labor market are separately highlighted, where a significant role is played by transformation processes caused by martial law, high labor migration, as well as low internal labor mobility. The interrelationships between various determinants are analyzed, as well as their impact on the structure of wages and social inequality. Emphasis is placed on the need to develop a scientifically based policy in the field of remuneration, which will reduce inequality and increase the efficiency of labor resources and the use of artificial intelligence in the context of digitalization. The article also emphasizes the importance of developing scientific research to solve practical problems related to the formation of fair and effective remuneration systems. Consideration of the determinants of remuneration as a scientific problem allows us to obtain a complete holistic picture of the mechanisms of wage formation and its impact on the socio-economic development of the country under martial law. Research into changes in determinants in remuneration policy allows us to obtain a holistic picture of the negative impact of military aggression on remuneration policy. Research into this problem is important for developing effective economic policy, optimizing available labor resources, and developing measures and motivational proposals for the return to Ukraine of labor migrants who were forced to leave it. The issues of building a holistic remuneration system in Ukraine under war conditions are also considered.
Keywords: determinants; remuneration; martial law; wages